3D library resources: a powerful tool in enhancing educational resources and student accessibility - Amno, Hasniza; Abdul Jais, Nurulhuda; Abdul Manan@Sulong, Husnaida; Zainol, Mohd Amin; Zainol, Zulkifli; Kamarul, Tunku (Universiti Teknologi Mara, Kedah, 2023)
The AMDI Library at the Universiti Sains Malaysia (USM) has initiated the transformative steps to introduce 3D library resources. Previously, users searched for information via the Koha library management system, which provided a bibliographic description of items. This library access was limited to physical resources such as books, graphics, anatomical models, videos, etc. Online 3D resources can be accessed from anywhere with an internet connection, making them highly accessible. Furthermore, online 3D resources can provide an engaging and immersive experience by interacting with virtual objects to enhance their learning and understanding. To materialize this, a 3D web portal called GoVR was created and integrated with Koha, providing a more comprehensive and immersive viewing experience and enhancing Koha’s functionality. The homegrown web-based system called "VR Discovery" is a 3D data management system that automatically transforms library resources into 3D format. These 3D resources are then transmitted and displayed on the GoVR web portal, designed responsively for different types of devices library users use. The development of VR Discovery considered information management, processing, analysis, and data production into 3D forms. The system has important characteristics such as search capabilities, security, and data homogeneity, with a specialized metadata template provided for each item of information. The VR Discovery system has made it easier for administrators to maintain library information resource records. The project initiatives have received valuable feedback from library users. This project is an innovative and creative 3D online learning platform for USM staff and students to access library information resources. It has a tremendous potential to be adapted by other academic libraries to enhance teaching and learning experiences to benefit both traditional and non-traditional learners.